PARP9 and PARP14 are involved in microglia-mediated neuroinflammation in Alzheimer′s disease - HUANG Lian, WEI Hui (Jichu yixue yu linchuang)
Objective To find specific mechanisms through which immune cell activation affects central nervous system inflammation in Alzheimer′s disease (Alzheimer′s disease, AD). Methods The public single-cell human brain database GSE161045 was applied for analysis. Then bulk RNA sequencing was performed in 5×FAD mice, and the results were validated using immunofluorescence staining microscopy with brain paraffin sections from 5×FAD mice. In the BV2 microglial cell line, AβOs were used to inducing activation and assessed the protein expression of PARP9 and PARP14 with Western blot. Finally, the relationship between PARP9 and PARP14 expression and immune infiltration was examined. Results In AD case, the expression of PARP9 and PARP14 was significantly up regulated (P＜0.000 1) in human brain immune cells, particularly in M2-type microglia. This result was confirmed by sequencing data from 5×FAD mice. Immunofluorescence staining of brain sections from 5×FAD mice showed up regulated expression of PARP9 and PARP14 in microglia surrounding Aβ plaques. Furthermore, in HMC3 cell line, activation induced by AβOs led to a significant increase in the protein expression of PARP9 and PARP14(P＜0.05). Conclusions The expression of PARP14 and PARP9 in microglia of AD patients and 5×FAD mice is significantly increased, and PARP9 and PARP14 positive microglia are significantly aggregated around Aβ plaques, indicating that PARP9 and PARP14 are potentially involved in the immune regulation of microglia on Aβ plaques and promote neuroinflammation in AD.